Konsep Kepemimpinan Profetik Dalam Pendidikan Agama Islam - Wahyu Ningsih; Asyifa Wasmin; Syifa Azhari (CV. ITTC INDONESIA, 2024)
The concept of prophetic leadership in Islamic religious education focuses on understanding and applying leadership principles that originate from prophetic teachings, especially those found in the Qur'an and Hadith. Prophetic leadership is not just the task of leading, but also carries the mission of educating and empowering individuals and communities to achieve moral, spiritual and social excellence In the context of Islamic religious education, prophetic leadership refers to the leadership model implemented by the Messenger of Allah and the Prophets. Islamic religious education aims to form individuals who are not only intellectually intelligent, but also have high morality in accordance with Islamic teachings. Prophetic leadership in Islamic religious education includes aspects such as example, integrity, justice, empathy, and concern for the holistic development of individuals. The principles of prophetic leadership are applied in the Islamic learning and teaching process, with teachers or educators as leaders who must provide good examples. The ability to inspire, listen, and respond to students' needs is the main key in prophetic leadership. Educators need to understand the demands of spirituality and morality of the Islamic religion, as well as provide encouragement to develop students' potential in achieving excellence as individuals and members of society. Thus, the concept of prophetic leadership in Islamic religious education emphasizes the formation of leaders who are not only academically competent, but also have strong moral and spiritual character in accordance with Islamic values. This approach is expected to be able to create an educational environment that empowers and forms a generation that can become agents of positive change in society.